Non-Alcoholic Fatty Liver Disease and Its Association with Cardiovascular Risk Factors: A Cross-Sectional Study - Ahmed, Faraz; Aimen, Umme; Mubashiruddin, Syed; Farshori, Sumaiya (International Journal of Medical Research, 2026)
Introduction: Non-alcoholic fatty liver disease is the most common chronic liver disease worldwide, closely associated with obesity, type 2 diabetes mellitus and metabolic syndrome. Beyond hepatic complications, NAFLD is increasingly recognized as a multisystem disorder with cardiovascular disease being the leading cause of mortality. The present study aimed to evaluate the prevalence of NAFLD and its correlation with cardiovascular risk factors. Methods: A retrospective cross-sectional analysis was conducted in Stoke-on-Trent, UK on 183 adult patients diagnosed with NAFLD by ultrasonography. Patients with significant alcohol intake, viral hepatitis, autoimmune or metabolic liver disease were excluded. Demographic, clinical, and biochemical data including cardiovascular risk factors were analyzed. Statistical tests included Chi-square, t-test/ANOVA, and binory logistic regression, with p <0.05 considered significant. Results: The mean age of participants was 44.8 ± 11.2 years, with a male predominance (64.5%). The most prevalent cardiovascular risk factors were obesity (74.9%) and dyslipidemia (66.1%), followed by hypertension (50.3%), diabetes mellitus (42.6%), and smoking (26.8%). Higher NAFLD grades were significantly associated with increased prevalence of hypertension, diabetes, and dyslipidemia. Biochemical parameters including fasting blood sugar, cholesterol, and triglycerides worsened with disease severity, while HDL levels declined (all p <0.05). Obesity, diabetes, and hypertension as independent predictors of advanced NAFLD. Conclusion: NAFLD is associated with obesity, diabetes, and hypertension, which also predict disease severity. These findings highlight the need for early screening, comprehensive risk assessment, and integrated management strategies to address both hepatic and cardiovascular outcomes in NAFLD patients.